Effects of exercise on paclitaxel-induced peripheral neuropathy in patients with cancer: A systematic review and meta-analysis - Mangaiyarakarasi Sekaran; Karthik S Udupa; Yash Alok; Ananth Pai; K Vasudeva Bhat (Cancer Research, Statistics, and Treatment)
Neuropathy caused by anti-cancer drugs such as paclitaxel significantly affects the quality of life in patients with cancer. Therefore, we summarized and evaluated existing studies to determine the effects of exercise on paclitaxel-induced peripheral neuropathy in patients with cancer. Our systematic review included only randomized controlled trials (RCTs) and secondary analysis of RCTs involving adult patients with cancer undergoing paclitaxel-based chemotherapy who participated in exercise interventions. We included English-language articles published between 1999-2023 from the Web of Science, EMBASE, Scopus, PubMed (Medline), and the Cumulative Index to Nursing and Allied Health Literature (CINHAL) [last search date for all databases: December 20, 2023]. Risk of bias assessment was conducted using Cochrane’s risk of bias tool for RCTs and the Jadad scale for trial quality independently by MS and YA, and dispute resolution was done by KSU. A total of 991 articles were retrieved across all databases, of which 301 articles were selected for title and abstract screening. Ultimately, 15 studies were included in the final analysis comprising a total of 1,148 patients. Data were tabulated based on differences in mean balance scores, sensory system scores, and quality of life scores between exercise and control groups. Both the results table and meta-analyses demonstrated that exercise had beneficial effects on balance [MD: 3.259 (1.948-4.571)], sensory symptoms, and quality of life [MD: 23.087 (1.760-44.414)]. Limitations of the review included a lack of data on the long-term benefits of exercise for chemotherapy-induced peripheral neuropathy (CIPN) symptoms. Additionally, sensitivity and subgroup analyses of pooled results were not possible. No external funding sources were used. The review was prospectively registered with PROSPERO’s International Prospective Register of Systematic Reviews (registration number: CRD42022333854).